INGLIZ TILI DARSLARIDA ZAMONAVIY USULLAR - Irgasheva Nasiba Dadajanovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is about teaching methods in English classes. The article talks about the grammatical, lexical and phonetic components of speech. The article also suggests methods for developing oral speech.